Indicators of Organizational Support in Implementing Maternal and Child Health Information System - Heru Santoso Wahito Nugroho; Stefanus Supriyanto; Hari Basuki Notobroto (Intelektual Pustaka Media Utama, 2016)
Nowadays, the implementation of health informtion system in Indonesia still encounters a number of obstacles e.g. redundant data, activities duplication, data quality, data not in harmony with the necessities, report not submitted on time, unoptimized feedback, low information utilization, and inefficient resources. This research aimed to analyze the indicators of organizational support which were suspected as one of the obstacles of the implementation of Maternal and Child Health Information System in Health Office of Ngawi Regency. The population of this cross sectional research was all village midwives administratively in duty in the areas of Ngawi Regency in 2015. Data was taken from all member of populaton through questionnaire filling, which was then analyzed by using confirmatory factor analysis (CFA). The result of data analysis suggested that the coefficient value that has been standardized from each indicators were as follows: supervisor support = 0.82, work condition = 0.80, and reard = 0.90. Indicators of organizational supportin implementing Maternal and Child Health Information System at Ngawi Regency Health Office, respectively from the most important are: reward, supervisor support, and work condition.